2011
DOI: 10.3389/fendo.2011.00044
|View full text |Cite
|
Sign up to set email alerts
|

Neurosteroids and GABA-A Receptor Function

Abstract: Neurosteroids represent a class of endogenous steroids that are synthesized in the brain, the adrenals, and the gonads and have potent and selective effects on the GABAA-receptor. 3α-hydroxy A-ring reduced metabolites of progesterone, deoxycorticosterone, and testosterone are positive modulators of GABAA-receptor in a non-genomic manner. Allopregnanolone (3α-OH-5α-pregnan-20-one), 5α-androstane-3α, 17α-diol (Adiol), and 3α5α-tetrahydrodeoxycorticosterone (3α5α-THDOC) enhance the GABA-mediated Cl- currents acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
113
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(118 citation statements)
references
References 342 publications
(522 reference statements)
2
113
0
3
Order By: Relevance
“…Studies have also demonstrated FAE-induced decreases in allopregnanolone potentiation of [ 3 H]flunitrazepam binding to hippocampal GABA A Rs in guinea pigs [100], age-dependent changes in a5 GABA A R subunit expression in mice [101], and increased d GABA A R subunit expression and sensitivity to THIP in cerebellar granule neurons of rats after early postnatal (P2-12) EtOH vapor exposure [102]. Neurosteroids, such as 3a,5a-3-hydroxypregnan-20-one (3a,5a-THP or allopregnanolone) and 3a;5a-tetrahydrodeoxycorticosterone (THDOC), are potent endogenous modulators of d subunitcontaining GABA A Rs [103]. Acute EtOH dynamically regulates local 3a,5a-THP levels in several subcortical regions of adult rats, independent of the adrenal glands [104,105].…”
mentioning
confidence: 99%
“…Studies have also demonstrated FAE-induced decreases in allopregnanolone potentiation of [ 3 H]flunitrazepam binding to hippocampal GABA A Rs in guinea pigs [100], age-dependent changes in a5 GABA A R subunit expression in mice [101], and increased d GABA A R subunit expression and sensitivity to THIP in cerebellar granule neurons of rats after early postnatal (P2-12) EtOH vapor exposure [102]. Neurosteroids, such as 3a,5a-3-hydroxypregnan-20-one (3a,5a-THP or allopregnanolone) and 3a;5a-tetrahydrodeoxycorticosterone (THDOC), are potent endogenous modulators of d subunitcontaining GABA A Rs [103]. Acute EtOH dynamically regulates local 3a,5a-THP levels in several subcortical regions of adult rats, independent of the adrenal glands [104,105].…”
mentioning
confidence: 99%
“…Neurosteroids exert their non-genetic functions mainly by enhancing the inhibitory effect of GABA A Rs [6][7][8]. To test whether they participated in the analgesic effect of neurosteroids, we injected bicuculline, a powerful GABA A R antagonist [37,38], into the lateral thalamus 0.5 h before the delivery of AC-5216, AP, or DOC.…”
Section: Gaba a Receptors Participated In The Analgesic Effects Of Nementioning
confidence: 99%
“…Neurosteroids have potent and selective effects on GABA A Rs [6][7][8]. PREG, PROG, and DOC are positive modulators in a non-genomic manner, while AP and THDOC potentiate synaptic GABA A R function and activate delta-subunit containing extrasynaptic GABA A Rs that mediate tonic currents [9,10].…”
Section: Gaba a Receptors Were Involved In The Analgesic Effect Of Nementioning
confidence: 99%
See 1 more Smart Citation
“…This binding forces a conformation where GABA displays a higher affinity increasing the frequency of opening of the ion channel [234]. Similarly, several neurosteroids such as allopregnanolone will bind to the GABA-A ionophore and force conformational changes enhancing GABA effects [235,236]. Immunohistochemical studies have shown dense staining in spinal Rexed laminae for several alpha, beta and gamma subunits likely corresponding to primary afferents [237,238] presumably localized on primary afferent terminals.…”
Section: Mechanisms Of Actionmentioning
confidence: 99%